## heathernelly 2 years ago ;;;;;;;;;;;;;

1. CalebBeavers

2. heathernelly

x=.75

3. heathernelly

it's not two equations, it's like one all together

4. CalebBeavers

Yeah, x= .75 isnt right. Solve for y in one of the equations, then plug that expression in for y into the other. Then you can solve for x

5. heathernelly

okay, one sec then

6. heathernelly

2.5x-3(3.25x-y)=-13? :S

7. CalebBeavers

You did that wrong. The purpose is to have one variable to solve for. You still have 2. lets solve for y in the second equation y=3.25x+14 now plug the expression into the other equation for y 2.5x-3(3.25x+14)=-13 now solve for x

8. CalebBeavers

2.5x-9.75x-42=-13 -7.25x=29 x=?

9. heathernelly

i had the math right, for some reason though, i put -13+42=27 :S oops. thanks! is that all i have to do?

10. CalebBeavers

What did you get for x? dont you wanna solve for y also?

11. heathernelly

-.25

12. heathernelly

just plug it into the second equation to get y? :/

13. CalebBeavers

If you're doing systems of equations i assume you should know how to solve a simple equation...i did all of it except one step.. x=29/-7.25 x=-4

14. CalebBeavers

Input -4 into one of the equations for x and then solve for y

15. heathernelly

thank youu (: